2005
DOI: 10.1111/j.1747-0765.2005.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

RhizobiumProliferation-Supporting Substances in Seed Exudates of Common Bean (Phaseolus vulgarisL.)

Abstract: Seed exudates collected from three cultivars (cv. Hokkaikintoki, Himetebou, and Kurodane‐kinugasa) of common bean (Phaseolus vulgaris L.) were fractionated based on several physicochemical properties, and the nutrient substances in the fractions effective for Rhizobium proliferation were determined. Regardless of the common bean cultivars, the low molecular weight and high polarity fraction showed the most beneficial effect on Rhizobium proliferation. After further separation of the low molecular weight and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In the case of P. vulgaris it contains several monosaccharides and oligosaccharides, almost all amino acids, some organic acids, but also proteins, enzymes and few anthocyanins and flavonoids (Morohashi & Shimokoriyama, 1972;Duke & Kakefuda, 1981;Hungria et al, 1991;Kato et al, 2005). Thus, the relatively negative isotopic signature found here for leaked organic compounds (-28.12 ± 0.076‰) is hard to relate to any particular metabolite, especially since the composition can vary considerably across varieties (Kato et al, 2005). This suggests that soluble compounds were noticeably 13 C-depleted compared with starch, which is consistent with the slight enrichment observed in seed organic matter on day 1, although the calculated isotopic impact of leaching on seed biomass is very low (i.e.…”
Section: Metabolic Changes In Different Organs Through Ontogenymentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of P. vulgaris it contains several monosaccharides and oligosaccharides, almost all amino acids, some organic acids, but also proteins, enzymes and few anthocyanins and flavonoids (Morohashi & Shimokoriyama, 1972;Duke & Kakefuda, 1981;Hungria et al, 1991;Kato et al, 2005). Thus, the relatively negative isotopic signature found here for leaked organic compounds (-28.12 ± 0.076‰) is hard to relate to any particular metabolite, especially since the composition can vary considerably across varieties (Kato et al, 2005). This suggests that soluble compounds were noticeably 13 C-depleted compared with starch, which is consistent with the slight enrichment observed in seed organic matter on day 1, although the calculated isotopic impact of leaching on seed biomass is very low (i.e.…”
Section: Metabolic Changes In Different Organs Through Ontogenymentioning
confidence: 99%
“…, 2005). Thus, the relatively negative isotopic signature found here for leaked organic compounds (–28.12 ± 0.076‰) is hard to relate to any particular metabolite, especially since the composition can vary considerably across varieties (Kato et al. , 2005).…”
mentioning
confidence: 99%
“…1997). Moreover, we indicated that this promotive effect was supported by large amounts of sugars and amino acids in the seed exudates (Kato et al. 2005).…”
Section: Introductionmentioning
confidence: 96%
“…1997). In addition, we showed that the promoting effect on rhizobial proliferation was supported by a large amount of sugars and amino acids in seed exudates (Kato et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1997) or within 24 h after culturing in the composed medium containing the seed exudates (Kato et al. 1997; Kato et al. 2005).…”
Section: Introductionmentioning
confidence: 99%